1987
DOI: 10.1016/0014-5793(87)80344-7
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human B cell stimulatory factor 2 (BSF‐2/IFN‐β2) regulates β‐fibrinogen and albumin mRNA levels in Fao‐9 cells

Abstract: Conditioned medium from human monocytes contains a partially characterized hepatocyte-stimulating factor that simultaneously elevates the mRNA levels of the acute-phase protein /3-fibrinogen and decreases albumin mRNA in rat hepatoma cells. We demonstrate that recombinant human B-cell stimulatory factor 2, which is identical to interferon-/?,?/26 kDa protein and interleukin-HPl, exhibits the same activity as hepatocyte-stimulating factor. Furthermore, a specific antibody against B-cell stimulatory factor 2 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
98
0
5

Year Published

1988
1988
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(105 citation statements)
references
References 28 publications
2
98
0
5
Order By: Relevance
“…Conversely huge amount of IL-6 is produced by established tumour cells and cause a state similar to cachexia to the mice when IL-6 producing tumour cells fail to be rejected. It is still unknown whether IL-6 directly induce hypoalbuminemia as has been reported in in vitro studies or whether a state similar to cachexia caused hypoalbuminemia secondly (Andus et al, 1987). In LLC-IL6 transplanted mice, splenomegary was observed and many megakaryocytes were seen in the spleen without attended thrombocytosis.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Conversely huge amount of IL-6 is produced by established tumour cells and cause a state similar to cachexia to the mice when IL-6 producing tumour cells fail to be rejected. It is still unknown whether IL-6 directly induce hypoalbuminemia as has been reported in in vitro studies or whether a state similar to cachexia caused hypoalbuminemia secondly (Andus et al, 1987). In LLC-IL6 transplanted mice, splenomegary was observed and many megakaryocytes were seen in the spleen without attended thrombocytosis.…”
Section: Resultsmentioning
confidence: 92%
“…IL-6 has many functions that may be of potential benefit for patients such as anti-tumour effect and stimulation of thrombopoiesis (Mule et al, 1990;Kitahara et al, 1990;Hill et al, 1990). However, other functions of IL-6 such as growth stimulation of myeloma, development of glomerulonephritis, induction of hypercalcaemia, inhibition of albumin synthesis may have adverse effect for patients (Bataille et al, 1989;Suematsu et al, 1989;Andus et al, 1987;Black et al, 1991). Thus, clinical benefit of IL-6 is controversial.…”
Section: Resultsmentioning
confidence: 99%
“…Hepatocyte-stimulating factor (HSF) [9,10], interleukin-1 (ILl) [11] and tumor necrosis factor (TNFc~) [12] are considered as being the major mediators of the acute-phase response. Recently, HSF and interleukin(IL)-6 (BSF2, IFNB2, 26 kDa protein and interleukin HP-1) were found to be functionally and immunologically identical [13,14]. In the rat hepatoma cell line Fao, acute-phase proteins are regulated differently by the mediators IL6, ILI~ and TNFce, indicating that the acute-phase response is more complex than previously described [15].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Baumann et al [7] demonstrated the existence of at least two types of HSF and showed that a combination of the two HSFs had the ability to induce overall acute-phase reactants, while the abilities of IL-l and TNF were limited to only a few sets of acute-phase reactants. In addition, it was recently reported that human Bcell stimulatory factor 2, which was identical to IFN-flu, had the ability to increase or decrease the hepatic mRNA level of fibrinogen or albumin, respectively [17]. From evidence that an antibody against B-cell stimulatory factor 2 inhibited this stimulatory activity in monocyte-conditioned medium, the authors suggested that B-cell stimulatory factor 2 or IFN-,& were identical to HSF [ 171.…”
Section: Discussionmentioning
confidence: 99%